Neural Underpinnings of Obesity: The Role of Oxidative Stress and Inflammation in the Brain - Caitlyn A. Mullins; Ritchel B. Gannaban; Md Shahjalal Khan; Harsh Shah; Md Abu B. Siddik; Vijay K. Hegde; P. Hemachandra Reddy; Andrew C. Shin (MDPI AG, 2020)
Obesity prevalence is increasing at an unprecedented rate throughout the world, and is a strong risk factor for metabolic, cardiovascular, and neurological/neurodegenerative disorders. While low-grade systemic inflammation triggered primarily by adipose tissue dysfunction is closely linked to obesity, inflammation is also observed in the brain or the central nervous system (CNS). Considering that the hypothalamus, a classical homeostatic center, and other higher cortical areas (e.g. prefrontal cortex, dorsal striatum, hippocampus, etc.) also actively participate in regulating energy homeostasis by engaging in inhibitory control, reward calculation, and memory retrieval, understanding the role of CNS oxidative stress and inflammation in obesity and their underlying mechanisms would greatly help develop novel therapeutic interventions to correct obesity and related comorbidities. Here we review accumulating evidence for the association between ER stress and mitochondrial dysfunction, the main culprits responsible for oxidative stress and inflammation in various brain regions, and energy imbalance that leads to the development of obesity. Potential beneficial effects of natural antioxidant and anti-inflammatory compounds on CNS health and obesity are also discussed.